A SWOT Analysis of Greenhouse Gas Emission Reduction Implementation at the Port of Tanjung Perak, Surabaya - Shofa Dai Robbi; Anugrah Nur Prasetyo; Prima Yudha Yudianto; M. Anjar Pamungkas (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Approximately 2.89% of the world’s carbon footprint can be attributed to the shipping sector. To mitigate this impact, the International Maritime Organization (IMO) established the MARPOL Annex VI regulations, which impose stringent limits on sulfur oxides (SO_x), nitrogen oxides (NO_x), and carbon dioxide (CO_2) emissions. As an archipelagic nation, Indonesia faces unique strategic and operational challenges in achieving regulatory compliance. This study evaluates the implementation of MARPOL Annex VI at Tanjung Perak Port, Surabaya, utilizing a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis framework. A mixed-methods approach was employed, integrating qualitative insights with quantitative data derived from stakeholder questionnaires. The analysis identifies key internal and external factors influencing the adoption of green shipping practices. Findings indicate that Indonesia’s transition requires a tripartite strategy: robust regulatory frameworks, technological innovation, and human capital development. Key recommendations include strengthening the enforcement of monitoring systems—specifically Measurement, Reporting, and Verification (MRV)—and introducing economic instruments such as an Emissions Trading System (ETS). Furthermore, the adoption of energy-efficient technologies and alternative marine fuels is critical. This research aligns with Sustainable Development Goals (SDGs) 7, 9, 13, and 14, providing a roadmap to enhance the maritime industry's competitiveness while contributing to global decarbonization targets.